Plyometric training for the lower limb - Woronczak, M. (1998)
Although the actual term "plyometric" is new, this particular form of training has been in existence for quite some time. The term was first applied in 1975 by American track and field coach Fred Wilt to describe the training methods of the Eastern European athletes at the time, which were the supposed difference between the eastern and western athletes. Translated from its Latin origins, it literally means "measurable increases" , although there is some speculation as to the effectiveness of this particular form of training. It is thought of as the missing link between weight training (strength) and athletic performance (power), with particular emphasis on the speed of activity. On observation of sports involving jumping at the elite level, particularly basketball, volleyball and the jumping field events, it is obvious that these athletes have the ability to spring very high indeed. Perhaps what is most striking is not how high they can rise, but how quickly they can elevate. Athletes such as Michael Jordan are able to translate from changing direction to releasing a jump shot extremely quickly. This has obvious advantages, especially in team sports such as basketball or volleyball. Plyometric training is designed to enable muscles to reach their maximum strength in as short a time as possible. Focus is placed on improving eccentric strength, achieving a rapid eccentric/concentric transition (termed amortization phase) and decreasing ground contact time using high force jumping exercises (for the lower limb). It has been shown that elite high jumpers spend only 0.12 seconds on the ground before a jump (Chu, 1992), indicating the need for minimal contact time. Jumping itself is a complex, multi joint and muscle skill, which must be learned. This form of training serves two main purposes - to improve existing jumping ability to enhance sporting performance and in recovery from injury. The eccentric exercise program as described by Stanish et al (1986) incorporates rapid eccentric exercises into the rehabilitation program, but does actually include sport specific or jumping exercises, which an athlete requires to return to their optimal level of functioning post injury. Thus, these techniques may be utilised as an extension to the program and to ensure that adequate rehabilitation has been performed prior to a return to sport. Unfortunately, there is a distinct lack of reliable scientific research conducted in this area, with little information available regarding the physiological basis, training effectiveness, or even the establishment of a standard protocol evident. Most information provided in books is written by physical educators with little knowledge or understanding of the human musculoskeletal system, or the principles of conducting proper scientific research. Even less information is found regarding the use of plyometric type exercises in a rehabilitation program.